2014
DOI: 10.5755/j01.ee.24.5.3309
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Values in Lithuania Police Organization: Managers‘ and Employees‘ Value Congruence

Abstract: Organizational values are long-term belief of what is right and what is wrong, and what is desirable and valuable in work situation. They dictate behaviour of members of the organization. Therefore, organizational values are a key element of organizational culture. The purpose of this paper is to present results from survey of the organisational values of Lithuanian police organization which is going through the process of organizational transfomation. That is why it is so important to identify how oficially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The priorities given to various work values may differ between different cultures, due to individual differences or the availability of resources in a particular police district or country (this is the case also for Maslow’s hierarchy of needs). Ruibyte and Adamoniene (2013) pointed out that a change in values may occur over time in post-transformation (that is after the fall of the iron curtain and the transformation to market-based capitalism) countries such as Lithuania, because of rapid changes in society, increased competition, and thus, more demanding work conditions. The current study was performed in Poland, which is a post-transformation country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The priorities given to various work values may differ between different cultures, due to individual differences or the availability of resources in a particular police district or country (this is the case also for Maslow’s hierarchy of needs). Ruibyte and Adamoniene (2013) pointed out that a change in values may occur over time in post-transformation (that is after the fall of the iron curtain and the transformation to market-based capitalism) countries such as Lithuania, because of rapid changes in society, increased competition, and thus, more demanding work conditions. The current study was performed in Poland, which is a post-transformation country.…”
Section: Discussionmentioning
confidence: 99%
“…Some situations in the work of police officers may be very stressful and require critical decision-making, and it is thus desirable to know which high-priority work values are shared by other police officers, at least in a specific culture or district. Furthermore, Ruibyte and Adamoniene (2013) showed that police officers valued work values other than effectiveness and productivity. In this profession the correct balance between extrinsic and intrinsic work values is particularly desirable because they are deeply held driving forces and they form the culture of the organization ( Wasserman and Moore, 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it becomes important to know and understand the high-priority work values of security officers. In addition, researchers also highlighted that security officers give more emphasis on work values than to productivity and effectiveness (Herrmann and Glaser, 2021; Ruibytė and Adamonienė, 2013). Thus, in this job role, stability in intrinsic and extrinsic attribution of work values is predominantly required, as values are sincerely held by them and work as driving forces in the culture of the organisation (Rattrie et al , 2020).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…One of the most influential researchers of organizational culture, Edgar Schein, brings out that organizational values are one of the key elements of organizational culture; according to them, we can understand and appreciate the culture of the organization itself, its specificity [30]. Organizational values determine organizational behaviour and culture [31]. Values are important in the organization because the resemblance in the perception of the same organizational values makes organizational culture effective and functioning [32].…”
Section: The Definition Of Organizational Level Values Is Generally Rmentioning
confidence: 99%